Jaan S. Islam and Adem Eryiğit (2022). Islam and The State in Ibn Taymiyya: Translation and Analysis. London: Routledge. 290 Pages. ISBN 978-1-032-13185-6 - Mulyani, Slamet; Maghfirotul Mukarom, Arik (Journal of Al-Tamaddun, 2024)
The concept of Islamic politics has undergone significant transformations from its traditional comprehension to its application in the modern context. Hence, it is crucial to look at the thoughts of influential figures in Islamic history to understand how this discourse evolved and its implications in the contemporary landscape. Ibn Taymiyya, a 14th-century Islamic theologian and philosopher, proposed profound insights into the concept of the Islamic state that continues to shape contemporary political discourse. Through his version of integrating Islamic law within political authority, Ibn Taymiyya laid the foundations for much of the modern Islamist ideology, influencing groups such as Salafis, Wahhabis, and Jihadist movements.